Prevalence and Factors Associated with Drug Resistance Among Pulmonary Tuberculosis Patients in a District of North Kerala - Dr. Suhail Neliyathodi; Dr. Jinsha Ap (Galore International Journal of Health Sciences and Research, 2026)
Background: Drug resistant tuberculosis (DR-TB) remains a major challenge to Tuberculosis (TB) control despite advances in diagnosis and treatment. Although Kerala has achieved better TB control outcomes than many other regions of India, district-level data on the prevalence and determinants of drug resistance are limited. This study estimated the prevalence and pattern of drug resistance among pulmonary TB patients in Malappuram district and explored factors associated with drug resistance. Methods: This cross-sectional study was conducted among bacteriologically confirmed pulmonary TB patients registered at the District TB Centre, Manjeri, Kerala, during 2024-2025. Information was obtained from the NIKSHAY portal and District TB Centre records after obtaining necessary administrative approvals. Universal sampling was adopted, and 960 patients were included. Drug resistance patterns were described using frequencies and percentages. Associations between clinical or behavioural factors and drug resistance were analysed using the chi-square test. Results: Among the 960 study participants ,675(70.3%) were males, and most cases were detected through passive case finding (97.1%). Rifampicin resistance was identified in four patients (0.42%), while isoniazid resistance was detected in 49 patients (5.10%). High-level isoniazid resistance (katG mutation) was present in 32 patients (3.33%) and low-level resistance (inhA mutation) was observed in 18 patients (1.88%). Fluoroquinolone resistance was detected in two patients (0.21%). Isoniazid resistance showed significant association with alcohol consumption, tobacco use, and household contact with pulmonary tuberculosis. No significant associations were observed for rifampicin or fluoroquinolone resistance. Conclusion: The prevalence of rifampicin and fluoroquinolone resistance in this district was considerably lower than national estimates, indicating effective implementation of TB control strategies in Kerala. However, the burden of isoniazid resistance highlights the need for early detection, appropriate treatment, strengthened contact investigation, and behavioural interventions targeting modifiable risk factors. Keywords: Pulmonary tuberculosis; drug resistance; isoniazid resistance; rifampicin resistance; NTEP; Malappuram; Kerala